Competition among banks and the pass-through of monetary policy - Jochen Güntner (Verein für Socialpolitik, 2010)
This paper introduces monopolistically competitive banks into the New Keynesian DSGE setting. I find that this contributes to explaining three empirical facts: (i) The short-run transmission of changes in monetary policy to bank retail rates is far from complete and heterogeneous. Stiffer competition among commercial banks implies that (ii) retail interest rates correlate more tightly with market rates, and (iii) loan rates exceed the policy rate less. My model predicts that augmented competition in the banking sector reduces the spread between the steady-state policy rate and the loan rate and amplifies the pass-through of monetary policy to the real economy.
Keywords: E32; E43; E51; 330; Monopolistically competitive banks; Collateral; External finance premium; Inside money premium